Trade competitiveness of palm oil downstream industry in Malaysia - Othman, Norashida (2019)
Palm oil industry is one of the key economic drivers and contributors to Malaysia’s national economy. It accounted for RM77.84 billion of export value in 2017, which was equivalent to 6.1% of national GDP. Despite the long history of the industry, the overall development of the palm oil industry in Malaysia has been below expectation. Currently, palm oil related exports are still highly dependent on the upstream segments such as crude palm oil (CPO) with a total contribution to the overall industry at 81.4% while that of downstream contribution is still low at about 18.6%. It is thus important to expand the production and export of high value-added palm oil downstream products such as oleochemicals, biodiesel and palm-based finished products. Therefore, the objectives of this study are: (i) to assess Malaysia’s relative competitiveness in palm oil downstream product as compared to 5 main producers of oils and fats (Indonesia, China, European Union-EU, the United States and Argentina); (ii) to analyse the potential market for Malaysian palm oil downstream products in 107 selected countries; (iii) to investigate the effect of environmental policy towards Malaysia’s competitiveness of palm oil downstream products. Three methodologies are employed namely relative trade advantage (RTA), shift-share analysis (SSA) and dynamic generalized method of moment (DGMM). The results indicate a higher and more stable relative trade advantage among Malaysia’s oleochemicals product while lower for finished products and biodiesel. For the potential market analysis, it is found that highest shift share percentage is in China (23.84%), followed by Republic of Korea (9.78%) and India (8.31%) for Malaysia’s oleochemical products. For palm-based finished products, China also ranks first for Malaysia’s most potential market with a net shift of 14.77% followed by Egypt (8.88%) and Nigeria (8.61%). The huge market potential is found in Spain for Malaysia’s biodiesel product with a net shift of 65.95% followed by Albania and Switzerland with a net shift of 15.91% and 5.57% respectively. The empirical analysis for the third objective based on Porter Diamond framework shows that all the main factors (i.e factor condition; demand condition; firm strategy and rivalry; and related supporting industry) significantly influence the competitiveness of the industry. Interestingly, the results also suggest that environmental regulations in EU have some positive impact on palm oil industry competitiveness, which is technically consistent with Porter Hypothesis which argues that more stringent environmental regulations can trigger innovation that may offset the costs of complying among the producer. The progress of palm oil downstream is crucial to improve the overall competitiveness of the palm oil industry and national economy. Therefore, this study highlights several policy recommendations which include better supporting facilities such as upgrading of logistic infrastructure, R&D facilities and training center related to palm oil downstream industry especially for biodiesel and palm-based finished products since both of these groups shows a decreasing trend of competitiveness. There is also an urgency to grab the opportunities to exploit the full potential of the oleochemical market since Malaysia is currently the most competitive in oleochemicals products as compared to other major producing countries of vegetable oils and fats. It is also recommended that Malaysia penetrate other emerging markets such as the Republic of Korea to take advantage of the growing market for cosmetics and personal care industries. Finally, it is also proposed that Malaysia’s government introduce the energy tax to promote the use of renewable energy leading to the sustainable production of palm oil and overall competitiveness of palm oil downstream industry.